2014
DOI: 10.4306/pi.2014.11.2.192
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Role of BDNF Val66Met and 5-HTTLPR Polymorphisms on Depressive Disorder

Abstract: ObjectiveWe investigated possible association between depressive disorders and BDNF Val66Met and 5-HTTLPR. Brain derived neurotrophic factor (BDNF) gene and serotonin transporter (SLC6A4) gene are promising candidate genes for depressive disorders. It has been suggested that BDNF promotes the survival and differentiation of serotonergic neurons and that serotonergic transmission exerts powerful control over BDNF gene expression.MethodsFinal analyses were performed on 186 patients with depressive disorders and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 38 publications
0
7
1
Order By: Relevance
“…Although a previous study showed a positive influence of the interaction between 5HTTLPR and a Val66Met substitution in brain-derived neurotropic factor on the age of onset of depressive disorder in the Korean population (Lee et al, 2014), ours is the first study showing a significant dose-dependent relationship between 5HTTLPR and the age of onset of MDD.…”
Section: Discussioncontrasting
confidence: 72%
“…Although a previous study showed a positive influence of the interaction between 5HTTLPR and a Val66Met substitution in brain-derived neurotropic factor on the age of onset of depressive disorder in the Korean population (Lee et al, 2014), ours is the first study showing a significant dose-dependent relationship between 5HTTLPR and the age of onset of MDD.…”
Section: Discussioncontrasting
confidence: 72%
“…Another possible reason behind the mixed results related to the genotype effect may be gene-gene interaction. A few studies suggested in fact that the BDNF genotype may interact with the catechol O-methyltransferase (COMT) and the serotonin transporter gene linked promoter region (5-HTTLPR) to produce differences in resilience 74 and onset age of depressive disorder 75 , respectively. Further studies investigating such a gene-gene interaction are needed, given that PTSD is known to be related to resilience 76 , depression 77 , and other psychological factors.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported both positive and negative results regarding the association between 5-HTTLPR and migraine/depression susceptibility (4247). In terms of migraine, for instance, Juhasz et al.…”
Section: Serotonin Transporter Slc6a4 and Tryptophan Hydroxylase 2 Tph2mentioning
confidence: 99%
“…A positive association was also identified from a recent meta-analysis (43) that showed that 5-HTTLPR was significantly associated with European female migraineurs carrying the s allele (OR: 2.02; 95% CI: 1.24–3.28). In terms of depression, a recent Korean study (44) detected that both the s allele and genotype frequencies of 5-HTTLPR were significantly associated with depression (adjusted p -value = 0.050 for allelic association; adjusted p -value = 0.015 for genotypic association). In a haplotype analysis (45), a significant association was reported between the 5-HTTLPR TA haplotype (tagging s allele) and MDD (OR: 1.14; 95% CI: 1.04–1.25).…”
Section: Serotonin Transporter Slc6a4 and Tryptophan Hydroxylase 2 Tph2mentioning
confidence: 99%